PENGARUH KEPADATAN KENDARAAN BERMOTOR TERHADAP KONSENTRASI KARBON MONOKSIDA AMBIEN (STUDI KASUS JALAN TAMAN SISWA YOGYAKARTA) - , EKO BAYU DHARMA PUTRA, Prof. Dr. H. A. Sudibyakto M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The study was conducted along Taman Siswa Road as the main source of emission centers. This study aims to determine the concentration of carbon monoxide in the Taman Siswa Road , knowing influence of vehicle density on the concentration of carbon monoxide , and determine the influence of climate parameter ( temperature , humidity , wind speed ) on the concentration of carbon monoxide. The method used in the study of data retrieval technique is the moving observation. Determination of sites using purposive sampling method. Measurements were performed in 9 main points along Jalan Taman students and 12 control points located 100 meters to the right and left main point. The analysis method used graph analysis and statistics analysis that is correlation, regression, and determination coefficient. The results of the study found that the highest concentration of carbon monoxide at 33 ppm and lowest at 14 ppm. Concentration of carbon monoxide is still under DIY ambient air quality standard is 35 ppm. The coefficient of determination between the density of vehicles on the concentration of carbon monoxide in the morning at 37.8 % , 21.1 % at the afternoon , 22.4 % at the evening, and the overall of 26.9 %. The coefficient of determination which shows the effect of temperature on carbon monoxide concentration 5.3 % at the morning , 11.3 % at the afternoon, 27.5 %at the evening , and 8.4 % overall. The coefficient of determination which shows the influence of moisture on the concentration of carbon monoxide at the morning gained 1,4 % , 11 % at the afternoon , 31.8 % at the evening, and 11.9 % overall. Determination coefficient that describes the influence of wind velocity on the concentration of carbon monoxide in the morning 0.1 % , 0.6 % at the afternoon , 32 % at the evening , and 9,6 % overall. Regression equation generated from this study the concentration of carbon monoxide = 4.414 + 0.137 (air humidity ) + 0.002 ( the density of motor vehicles). Grounded on the regression equation,maximum vehicle density who going across Taman Siswa Road is 11284 smp/hours